Marriage Registration for All Religions at the Office of Religious Affairs: Between Debate and Promoting Moderation - Rifqi, Muhammad Jazil (Islamic Family Law Department, Sharia and Law Faculty, UIN Sunan Ampel Surabaya, Indonesia, 2024)
The Office of Religious Affairs (KUA), which operates in sub-districts across Indonesia, currently serves marriage registration only the Muslim community, while non-Muslims must register in the district-based Civil Registry Office. Recently, the Minister of Religious Affairs has proposed transforming KUA into a marriage registration center for all religions, which has provoked criticism. This study explores how the debate about inclusive marriage registration services runs in the media while examining the promotion of moderation in its services. Using a historical and sociological approach, it finds that, historically, during the Dutch East Indies period, non-Muslims registered marriages at the Burgerlijk Stand, while Muslims went to the Kantor Voor Inslanche Zaken/Shumubu. Expanding KUA's role to all religious marriages raises significant regulatory challenges and elicits mixed reactions. Critics argue this change may compromise the sacredness of religious marriage rites and alter KUA's traditional role. At the same time, supporters see it as a way to simplify marriage administration, especially in remote areas. The study suggests that the legacy of Dutch colonial legal practices (rechtstelsel) should be reassessed and adapted to address modern needs, aiming for a legal framework that ensures good governance through legal certainty, utility, and public interest alignment.